Dietary glucose regulates yeast consumption in adult Drosophila males - Lebreton, Sébastien; Witzgall, Peter; Olsson, Marie; Becher, Paul G. (Frontiers in Physiology, 2014)
The adjustment of feeding behavior in response to hunger and satiety contributes to homeostatic regulation in animals. The fruit fly Drosophila melanogaster feeds on yeasts growing on overripe fruit, providing nutrients required for adult survival, reproduction and larval growth. Here, we present data on how the nutritional value of food affects subsequent yeast consumption in Drosophila adult males. After a period of starvation, flies showed intensive yeast consumption. In comparison, flies stopped feeding after having access to a nutritive cornmeal diet. Interestingly, dietary glucose was equally efficient as the complex cornmeal diet. In contrast, flies fed with sucralose, a non-metabolizable sweetener, behaved as if they were starved. The adipokinetic hormone and insulin-like peptides regulate metabolic processes in insects. We did not find any effect of the adipokinetic hormone pathway on this modulation. Instead, the insulin pathway was involved in these changes. Flies lacking the insulin receptor did not respond to nutrient deprivation by increasing yeast consumption. Together these results show the importance of insulin in the regulation of yeast consumption in response to starvation in adult D. melanogaster males.